Association between short-term nitrogen dioxide exposure and outpatient visits for anxiety: A time-series study in Xi'an, China. (15th June 2022) - Zhou, Yumeng; Xu, Chen; Zhang, Yao; Zhao, Mengxue; Hu, Yuegu; Jiang, Yuexu; Li, Dawei; Wu, Na; Wu, Long; Li, Chengying; Li, Yafei; Ji, Ailing; et al.
Abstract: As the most common mental disorder, anxiety heavily damages human mental health and leads to heavy health burdens. However, evidence concerning the impact of NO2 on anxiety is limited. In this study, we aimed to further explore the association between short-term NO2 exposure and anxiety outpatient visits in Xi'an, a city located in Northwest China with relatively heavy air pollution. Daily data of anxiety outpatient visits, air pollutants (PM2.5, PM10, SO2, NO2, CO, and O3 ), and meteorological conditions (daily mean temperature and relative humidity) from 2013 to 2019 were gathered. Then generalized additive models (GAM) was adopted to investigate the relationship between short-term NO2 exposure and the number of anxiety outpatient visits after controlling for long-term effects, holiday effects, day of the week, and weather conditions. The results showed that NO2 exposure was positively correlated with the number of daily anxiety outpatient visits: A 10 μg/m 3 increase of NO2 concentration corresponded to 1.94% (95%CI: 1.19%, 2.68%) and 3.72% (95%CI: 2.35%, 5.08%) increase in anxiety outpatient visits at lag 1 and lag 07, respectively. Such a relationship showed gender differences (more obvious in females) but no age differences. More interestingly, the association between NO2 and anxiety outpatient visits showed to be more obvious during cool seasons than during warm seasons. In summary, short-term ambient NO2 exposure, especially during cool seasons, may be related to a higher risk of anxiety outpatient visits. Highlights: Short-term NO2 exposure was associated with outpatient anxiety visits. The association only significant in the cool seasons. The association was more obvious in females than in males.